First principles study on properties of dopants and defects of palladium and niobium with gas molecules on graphene-based materials using density functional theory / Maisaratul Shamimi Muhamad Shukri - Muhamad Shukri, Maisaratul Shamimi (2024)
Gas monitoring technologies are in demand in the nanotech field as they are necessary for detecting flammable and hazardous gases. Graphene is widely used in sensing technology due to its fascinating electronic properties. However, the compatibility of graphene with nanoelectronic devices is low and needs to perform better due to its 2D structure and zero band gap properties. Hence, we present this theoretical study on enhancing the properties of graphene as a gas monitoring sensor in sensing lethal gas molecules to prevent air pollution. The structural and electronic properties of graphene and defect graphene upon gas molecular adsorption are determined by performing the first-principle ab initio density functional theory (DFT) calculation.